2020
DOI: 10.1038/s41586-020-2550-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-specific T cell immunity in cases of COVID-19 and SARS, and uninfected controls

Abstract: Memory T cells induced by previous pathogens can shape susceptibility to, and the clinical severity of, subsequent infections 1. Little is known about the presence in humans of pre-existing memory T cells that have the potential to recognize severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Here we studied T cell responses against the structural (nucleocapsid (N) protein) and non-structural (NSP7 and NSP13 of ORF1) regions of SARS-CoV-2 in individuals convalescing from coronavirus disease 2019 (COV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

171
2,179
10
33

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,963 publications
(2,478 citation statements)
references
References 29 publications
171
2,179
10
33
Order By: Relevance
“…In 39 uninfected HCWs largely exposed to COVID-19 patients, we demonstrated a consistent and polyfunctional production of cytokines in response to SARS-CoV-2 peptides, covering viral structural proteins S, M and N, that was similar to that observed in 17 convalescent HCWs, adjusted by age and sex. These ndings are in agreement with other works focused on SARS-CoV-2-speci c T cells that started to be characterized in COVID-19 patients and uninfected individuals [15][16][17][18][19][20] . Le Bert et al found speci c cellular responses in recovered patients and uninfected individuals mainly to structural protein (NP) and nonstructural proteins (NSP), although NPS response was rarely detected in SARS-COV-2 recovered individuals, measured by the production of IFN-γ and TNF-α by CD4 and CD8 T cells 17 .…”
Section: Discussionsupporting
confidence: 93%
“…In 39 uninfected HCWs largely exposed to COVID-19 patients, we demonstrated a consistent and polyfunctional production of cytokines in response to SARS-CoV-2 peptides, covering viral structural proteins S, M and N, that was similar to that observed in 17 convalescent HCWs, adjusted by age and sex. These ndings are in agreement with other works focused on SARS-CoV-2-speci c T cells that started to be characterized in COVID-19 patients and uninfected individuals [15][16][17][18][19][20] . Le Bert et al found speci c cellular responses in recovered patients and uninfected individuals mainly to structural protein (NP) and nonstructural proteins (NSP), although NPS response was rarely detected in SARS-COV-2 recovered individuals, measured by the production of IFN-γ and TNF-α by CD4 and CD8 T cells 17 .…”
Section: Discussionsupporting
confidence: 93%
“…In line with other recent reports, we also observed in one unexposed donor very low frequencies of CD4 + and CD8 + T cells against spike and nucleocapsid proteins, respectively, probably due to cross-reactive cells primed against other SARS viruses [12][13][14]. We also used m24 Ab staining to con rm the induction of anti-vaccine CD4 + T cells after experimental immunization of a healthy volunteer with synthetic peptides from the spike and nucleocapsid proteins [9].…”
Section: Discussionsupporting
confidence: 89%
“…However, much less is currently known regarding the SARS-CoV-2-speci c T cell response, in particular which parts of the virus are targeted by T cells. Both CD4 and CD8 T cells can recognize SARS-CoV-2 derived antigens 4,[6][7][8][9][10][11][12][13] . Most studies have focused on limited parts of the viral proteome 6,8,12 , and in particular the spike protein 4,10,13 , which was found to be a very important antigen source for virus speci c T cell responses in SARS-CoV-1 14 and MERS 15 .…”
Section: Introductionmentioning
confidence: 99%